2012
DOI: 10.1161/circep.112.973339
|View full text |Cite
|
Sign up to set email alerts
|

Shock Efficacy of Subcutaneous Implantable Cardioverter-Defibrillator for Prevention of Sudden Cardiac Death

Abstract: However, with the increasing application of transvenous ICDs and higher patients' life expectancy, long-term technical difficulties, such as lead failure or device infection, have become important issues in clinical practice. [2][3][4] In addition, complications during lead placement, such as lead dislocation, perforation, or pneumothorax, bear a substantial perioperative risk. 5 The subcutaneous ICD (S-ICD) offers an alternative, novel approach to avoid lead-associated complications. 6 A first report from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 18 publications
2
62
0
1
Order By: Relevance
“…Our study had similar results and had more spontaneous events along with the chronic conversion study for induced VF that is additive to the literature of S-ICD System experience. A recent article 19 from Germany evaluating 40 patients with the S-ICD System demonstrated a lower first shock efficacy for spontaneous episodes. However, this was in only 4 patients (10%) with idiopathic VF and may represent an outlier population of patients compared with the ≈83% first shock efficacy in this larger, more diverse cohort of primary prevention patients with well-monitored prospective follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Our study had similar results and had more spontaneous events along with the chronic conversion study for induced VF that is additive to the literature of S-ICD System experience. A recent article 19 from Germany evaluating 40 patients with the S-ICD System demonstrated a lower first shock efficacy for spontaneous episodes. However, this was in only 4 patients (10%) with idiopathic VF and may represent an outlier population of patients compared with the ≈83% first shock efficacy in this larger, more diverse cohort of primary prevention patients with well-monitored prospective follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Terapia z powodu VT lub VF została zastosowana w 169 z tych przypadków (53%) i tylko 1 pacjent zmarł z powodu nawracającego VF i znacznej bradykardii [161]. Próby kliniczne z użyciem podskórnych ICD podsumowano w dodatkowej tabeli 6 [157][158][159][160][161][162][163][164][165].…”
Section: Podskórny Implantowany Kardiowerter--defibrylatorunclassified
“…Recognizing the caveat that this approach does not provide chronic pacing support, the efficacy of S-ICD has been proven in multiple studies. [22][23][24][25][26][27][28] Eligibility in CHD Patients for S-ICD The potential eligibility of CHD patients for S-ICD has been reported in a small 30-patient cohort that screened 10 patients with tetralogy of Fallot, 10 patients with transposition of great arteries and 10 patients with single ventricle/Fontan circulation. 14 This screening was compared with 10 control patients without CHD, and it was found that 87% of CHD patients vs. 100% of the controls met S-ICD eligibility.…”
Section: Inverted T Wave In Precordial Lead As Predictor Of Screeningmentioning
confidence: 99%